VALIDITY AND LEGAL POSITION OF ON-CHAIN DISPUTE RESOLUTION IN THE INDONESIAN ARBITRATION SYSTEM: A COMPARATIVE ANALYSIS WITH SINGAPORE LAW - Daffa Charisma Putra Ramadhon (RADJA PUBLIKA, 2026)
The development of blockchain technology has given rise to on-chain dispute resolution (OCDR) as a dispute settlement mechanism that operates entirely through algorithms and anonymous jurors, without the involvement of any state judicial institution. This research aims to analyze the legal standing of OCDR within Indonesia's civil law system and examine its validity as a form of arbitration under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, enriched through a comparative analysis with Singapore's legal framework. This research employs a normative juridical method enriched with comparative elements, utilizing the theory of Lex Cryptographia, the theory of state sovereignty and legal positivism, and Satjipto Rahardjo's progressive law theory as analytical tools. The findings indicate that OCDR constitutes a sui generis legal phenomenon operating as Lex Cryptographia, an independent normative order born from algorithmic consensus rather than sovereign state authority. This characteristic causes OCDR to encounter structural deadlock when tested against the legal positivism paradigm underlying Indonesia's Arbitration Law, particularly concerning the validity of arbitration agreements and arbitrator qualifications, both of which remain fundamentally human-centric. Comparison with Singapore reveals that even a more technology-accommodating legal framework experiences similar normative friction, albeit at a lower intensity. This research argues that Satjipto Rahardjo's progressive law approach which prioritizes the law's benefits to humanity over their textual compliance, provides a relevant philosophical framework to justify the acceptance of a hybrid arbitration model, as successfully demonstrated in the Kleros case in Mexico, as a pragmatic solution to the legal gap currently faced by Indonesia.